Coal bed methane : from prospect to pipeline - Aminian, Kashy; Schatzel, Steven J.; Thakur, Pramod (Elsevier, 2014)
Coal Bed Methane: From Prospect to Pipeline is the proceedings of the 25th anniversary of the North American Coal Bed Methane Forum. It provides the latest advancements in the production of coal bed methane covering a variety of topics, from exploration to gas processing, for commercial utilization. Additionally, it presents the origin of gas in coal, reservoir engineering, control of methane in coal mines, production techniques, water management, and gas processing. The vast coal resources in the United States continue to produce tremendous amounts of natural gas, contributing to a diverse range energy assets. Following a rapid advancement and subsequent plateau in technological developments, this book captures the full life cycle of a well and offers petroleum geologists and engineers a single source of a broad range of coal bed methane applications. This book addresses crucial technical topics, including exploration and evaluation of coal bed reservoirs; hydraulic fracturing of CBM wells; coal seam degasification; and production engineering and processing, among others. It also covers legal issues, permitting, and economic analysis of CBM projects.